QseC Inhibition as a Novel Antivirulence Strategy for the Prevention of Acute Hepatopancreatic Necrosis Disease (AHPND)-Causing Vibrio parahaemolyticus - Yang, Qian; Zou, Peizhuo; Cao, Zhi; Wang, Qingyao; Fu, Songzhe; Xie, Guosi; Huang, Jie (Frontiers in Cellular and Infection Microbiology, 2021)
Acute hepatopancreatic necrosis disease (AHPND) caused by Vibrio parahaemolyticus resulted in great economic losses in global shrimp aquaculture. There is an urgent need for development of novel strategies to combat AHPND-causing V. parahaemolyticus (VpAHPND), given that one of the greatest challenges currently is the widespread use of antibiotics and subsequent emergence of multidrug-resistant bacteria. Here, we proposed a broad-spectrum antivirulence approach targeting a conserved histidine kinase, QseC, which has been demonstrated to activate virulence expression in several Gram-negative pathogens. Our results showed that QseC mediated the catecholamine stimulated effects on growth and flagellar motility of VpAHPND. Transcriptome analysis revealed that QseC was involved in the global regulation of the virulence of VpAHPND as the ΔqseC mutant exhibited a decreased expression of genes related to type IV pilin, flagellar motility, and biofilm formation, while an overexpression of type VI secretion system and cell wall biosynthesis. Subsequently, the bacterial catecholamine receptor antagonist LED209 not only neutralized the stimulatory effects of host catecholamines on the growth and motility of VpAHPNDin vitro, but also attenuated the virulence of VpAHPND towards brine shrimp larvae and white shrimp in vivo. Additionally, LED209 presented no interference with pathogen growth, nor the toxicity to the experimental animals. These results suggest that QseC can be an attractive antivirulence therapy target, and LED209 is a promising candidate for development of broad-spectrum antivirulence agents. This is the first study that demonstrated the role of QseC in the global regulation of VpAHPND infection and demonstrated the antivirulence potential of LED209, which provides insight into the use of an antivirulence approach for targeting not only VpAHPND, but also a much larger collection of pathogenic bacteria.